PERLINDUNGAN HUKUM TERHADAP SAKSI PENGUNGKAP FAKTA (WISHTLE BLOWER) DALAM PERKARA TINDAK PIDANA KORUPSI - , Bambang Sujatmiko ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study is to find relevant answers of two questions about the Witness Protection Law Against Facts discloser (Wishtle Blower) In Case of Corruption Act: First, how the form of legal protection of witnesses expressing the facts in the case of corruption according to positive law? Second, how should the law on witness protection arrangements in expressing the facts of corruption crimes in the future? The method used in this study is normative and legal research methods supported by the methods of empirical legal research. The location is used as a research site is the Witness and Victims Protection Agency in Jakarta, the Corruption Eradication Commission in Jakarta, Provincial Police Special Region of Yogyakarta, Yogyakarta Legal Aid Institute, Yogyakarta State Attorney and the Centre for Human Rights Islamic University of Indonesia in Yogyakarta. Based on the results data analysis of these studies it can be concluded: First, in the positive force law in Indonesia, there are not regulations that specifically cover protection of witnesses facts discloser(whistle blower), but still a general nature that is the protection of witnesses and victims. Form of witness protection in Law No. 13 of 2006 on Protection of Witnesses and Victims are the protection of personal security, family and property and freedom from threats associated with the testimony has been granted, participate in the process of selecting and determining the shape protection and security support, provide information without pressure, obtain an interpreter, free of the questions that ensnare, obtain information on the development of the case, obtain information regarding a court decision, notified when prisoners were released, get a new identity, get a new residence, reimbursement of transportation costs, get legal adviser, and obtain assistance while living expenses to the extent of protection expires. Second, the absence of regulations specifically governing the protection of witnesses facts discloser(whistle blower) and the fact about the fate of the complainant because of the threat of either physical or psychological as well as efforts to criminalize witnesses and victims or their families, making people afraid to give testimony to law enforcement. Nonetheless, not required special legislation governing whistle-blowers, but to revise Law No.. 13 in 2006 to more accurately discuss the protection of whistle blowers so that no collisions occur due to the issuance of regulations that the new legislat